The governance and management of public library services in Nigeria. Issue 6 (13th August 2018) - Salman, Abdulsalam Abiodun; Mostert, Janneke; Mugwisi, Tinashe
Abstract : Purpose: The purpose of this paper is to explore the managerial and governance issues that impact on service delivery in public libraries in Nigeria. Within many countries this seems to be a challenge often resulting in an ineffective service delivery resulting in underutilisation thereof. This study was conducted among administrators and managers of public libraries in Nigeria to establish the current status quo concerning governance and management issues impacting on service delivery. Design/methodology/approach: A qualitative study using interviews was used to illicit data from three permanent secretaries, six public library directors, and six heads of rural community libraries, purposively selected for the study. Findings: The findings show that variables such as relevant academic qualifications, years of experience, and designation of the administrators and managers of public libraries affect service delivery. A huge dependency on government bodies for decision making and funding was established. Impediments to good management of the libraries were found to be inadequate funding; lack of involvement of stakeholders in public library administration; and inappropriate public library legislation. Practical implications: The study recommends the promulgation of a public library-specific act in order to regulate the administration and management of this public unit, involve stakeholders in public library administration, as well as the provision of alternative forms of funding in order to alleviate the dependence on governmental budgets. Originality/value: With very little research available on these issues in Nigeria, this paper will create awareness among all stakeholders of specific governance and managerial issues impacting on effective service delivery to public library users so that it can be addressed.